An Evaluation of In vivo Sensitivity via Public Monitoring - Webb, J.L.; Kirchner, T.B. (Radiation protection dosimetry, 2000)
Citizen volunteers from the Carlsbad, New Mexico area were monitored for internally deposited radionuclides through a project entitled 'Lie Down and Be Counted'. This project is provided as an outreach service to the public to support education about naturally occurring and man-made radioactivity present in people and the environment prior to the opening of the Waste Isolation Pilot Plant (WIPP). The bioassay measurements consisted of a lung and whole-body count. Prior to their bioassay, each subject completed a lifestyle questionnaire which included questions regarding their age, sex, weight, height, ethnicity, occupation, foreign travel, wild game consumption, smoking habit and any nuclear medicine procedures. Since a majority of these radionuclides were not detectable in local residents, a primary focus of the study was to evaluate the variability of human background and the implications with respect to measurement sensitivity.